Implementation of the Design Thinking Method in the Design of Mobile-Based MSME Applications (Case Study of MSME Mooara Space in Muara Badak District) - Muhammad Risqi Zharfan; Azahari Azahari; Ahmad Abdul Khair (STMIK Widya Cipta Dharma, 2026)
This study aims to design a mobile-based application for Micro, Small, and Medium Enterprises (MSMEs) to support digital transformation and improve service efficiency. Mooara Space MSME in Muara Badak District currently experiences limitations in managing services and delivering product information due to the absence of an integrated digital system. This condition leads to inefficiencies in operations and limited accessibility for customers. To address this issue, this research applies the Design Thinking approach, which emphasizes User-centered problem solving based on real needs and experiences. The research process consists of five main stages: empathize, define, ideate, prototype, and test. Data collection was conducted through direct observation and interviews with business owners and customers to identify key challenges and expectations. The findings were then translated into system requirements and solution concepts, which were implemented into a mobile application prototype. The developed application includes features such as product catalog, order management, payment processing, and order tracking. The evaluation results indicate that the proposed solution is able to meet User needs and improve interaction efficiency between customers and the business. Therefore, the application design is expected to enhance service quality, increase customer engagement, and support sustainable digital adoption for MSMEs.